Design of biology teaching materials based on discovery learning with scientific approach for class 10th in senior high school - Binerd Anthon Im Toy; Ferry F Karwur; Junet F. da Costa; Jerry F Langkun; Ferdy S Rondonuwu (Universitas Negeri Jakarta, 2018)
Indonesia as a tropical country with two seasons and has a high humidity into a good land for mushrooms growth. Students need to be taught to understand mushrooms. Understanding includes; morphology, physiology, reproduction, roles, and benefits of fungi. Discovery learning with a scientific approach becomes one of the active methods for, providing learning to Senior high school-class 10th students. Methods of scientific approach are done through activities: observing, asking, trying, reasoning, and communicating. A biology lesson that is active, innovative, creative, effective, and fun for the learners depends on the approach chosen and the instructional method used. The purpose of the development of this learning material was to design a biology instructional module on fungi using discovery learning with scientific approach. A scientific approach is a learning approach conducted through the following activities: observing, asking questions, experimenting, analyzing, and communicating. One method that is relevant with the principles of scientific approach is discovery learning. The stages in discovery learning are: stimulation, problem identification, data collection, data processing, providing evidence, and drawing conclusion. This biology lesson based on discovery learning with scientific approach complemented with pictures has the potentials in increasing the learning of the learners because they will be able to organize and conduct experiments to discover new knowledge